Clinical experience with rosuvastatin in the management of hyperlipidemia and the reduction of cardiovascular risk. (November 2011) - Nicholls, Stephen J; Uno, Kiyoko; Kataoka, Yu
On the basis of large randomized clinical trials, pharmacological antagonists of HMG-CoA reductase (statins) have become increasingly used in clinical practice for the prevention of cardiovascular disease. Rosuvastatin was developed as a potent statin, which appeared to raise levels of HDL-cholesterol, in addition to marked reductions in levels of LDL-cholesterol. These effects on lipids are associated with a beneficial impact of rosuvastatin on progression of various stages of atherosclerosis and cardiovascular outcomes in clinical trials. The clinical experience of rosuvastatin will be reviewed in this article.